AGRICULTURE GRADUATES’ EMPLOYMENT PROFILE AND FEEDBACK ON CURRICULUM - Ceniza, Ryan P; Alera, Evelyn Q; Nicolas, Honeylet J; Tejada, Rael C; Mendoza, Julita P (Journal of Agriculture and Technology Management, 2021)
Tracer studies are essential in evaluating curricular programs, including agricultural courses whose graduates face a changing labor market. This study aimed to determine BS Agriculture graduates’ employment profile, feedback on the adequacy of curriculum, and satisfaction with competencies acquired from the program. A total of 74 alumni from Batch 2018 was selected via simple random sampling to respond to the questionnaire adapted from the Commission on Higher Education Graduate Tracer Study Questionnaire. Results showed that graduates have a 98.5% employment rate, mostly employed through their initiative (66%), on a contractual status (73%), related to agriculture (68%), locally employed within the Philippines (96%), and whose career plans are to be promoted at the current job (57%). The majority of graduates rated the overall adequacy of the BSA curriculum as either adequate (51%) or very adequate (42%) and were mostly satisfied with the professional competencies, personal attributes, and management or leadership skills they developed from the curriculum. Significant associations are observed in the perceived overall adequacy of curriculum, and development of graduates’ professional competencies, personal attributes, and management skills. The curriculum of the program has contributed significantly to the employability of the agriculture graduates and has enabled them to acquire jobs related to their degree. However, with the present shift of employment trends globally, the curriculum is suggested to be updated and revised to better prepare graduates in meeting the current demands of the labor market.